Social media marketing and its benefits in msmes (Revista de Investigaciones Universidad del Quindío, 2022)
The present work aims to analyze the influence of the use of Social Media (SM) tools in Micro, Small and Medium Enterprises (MSMEs) in the state of Tabasco, in order to propose a model that favors commercialization. Social networks as part of Digital Marketing (DM) and in particular SM, have become a very important marketing tool for the vast majority of companies. The internet, technological development and Social Media have caused a revolution in the world's markets, in such a way that companies have the imperative to adopt them. In this regard, the following question arises: What is the influence of the use of the SM on the benefits of returns in the MSMEs of the state of Tabasco? This research is non-experimental, transversal with a quantitative approach, proposes a confirmatory-explanatory scope, and uses Structural Equation Systems (SEM) as a statistical method to test its hypotheses. The model for this research is formative causal structural. The study population is the MSMEs of the state of Tabasco, the type of sampling is non-probabilistic, the sample is 310 and a 19-item survey is used. The results revealed that, for each unit of time of use of the SM tools, 0.448 of performance benefits are acquired. In conclusion, the use of the SM has a significant and positive influence on the performance benefits of MSMEs.
Keywords: Digital Marketing; Social Media; Social Media Marketing; SME´s